2018
DOI: 10.1186/s12944-018-0852-z
|View full text |Cite
|
Sign up to set email alerts
|

Exercise without dietary changes alleviates nonalcoholic fatty liver disease without weight loss benefits

Abstract: BackgroundThis study aimed to analyze the effect of exercise and/or dietary change on improvement of non-alcoholic fatty liver disease (NAFLD) in chronic high-fat diet (HFD)-induced obese mice.MethodsForty male C57BL/6 (8 weeks old) mice were divided into normal diet (CO, n = 8) and high-fat diet (HF, n = 32) groups. The HF group was fed with 60% fat chow for 16 weeks to induce obesity. After the obesity induction period, the HF group was subdivided into HFD + sedentary (n = 8), HFD + training (HFT, n = 8), di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 36 publications
6
32
0
1
Order By: Relevance
“…Previous studies have shown that aerobic or resistance exercise alone can alleviate obesity and metabolic disorders. Aerobic exercise reduced obesity in obese mice; reversed insulin resistance; improved blood glucose levels, blood lipid disorders and liver metabolic disorders in obese mice; reduced the inflammation of adipose tissue; and reduced cardiovascular risk (35)(36)(37)(38)(39). Twelve weeks of resistance exercise improved weight loss and glucose tolerance in obese mice and reduced endoplasmic reticulum (ER) stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that aerobic or resistance exercise alone can alleviate obesity and metabolic disorders. Aerobic exercise reduced obesity in obese mice; reversed insulin resistance; improved blood glucose levels, blood lipid disorders and liver metabolic disorders in obese mice; reduced the inflammation of adipose tissue; and reduced cardiovascular risk (35)(36)(37)(38)(39). Twelve weeks of resistance exercise improved weight loss and glucose tolerance in obese mice and reduced endoplasmic reticulum (ER) stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate-intensity resistance training prevented cardiovascular diseases caused by obesity. The underlying mechanism of the effects of exercise included increasing AMPK, CPT1 expression, the phosphorylation of AMPK and ACC; increasing the phosphorylation of AKT, AKT and ERK expression; the endothelial nitric oxide synthase (eNOS) induction of fatty acid b-oxidation and lipogenesis inhibition following increased AMPK-a activity, thereby activating key enzymes that promote lipid metabolism (36)(37)(38)(39)(40)(41). Abnormal expression of the phosphorylation of ACC and CPT1 indicates increased fatty acid uptake and reduced oxidative utilization (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of animals and human studies suggested that regular exercise might be effective in alleviating NAFLD even if weight loss does not be induced. Some previous studies reported that exercise without dietary or caloric restriction did not affect weight loss [13,14]. Although there was no bene t of weight reduction, regular aerobic exercise increased lipolytic proteins in the liver and improved glucose tolerance in HFD-induced obese mice [13].…”
Section: Introductionmentioning
confidence: 95%
“…Some previous studies reported that exercise without dietary or caloric restriction did not affect weight loss [13,14]. Although there was no bene t of weight reduction, regular aerobic exercise increased lipolytic proteins in the liver and improved glucose tolerance in HFD-induced obese mice [13]. A Previous human study also reported that four weeks of aerobic exercise led to a decrease in hepatic triglyceride concentration and visceral adiposity in obese individuals without weight loss [14].…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, não foi possível observar melhora histológica do fígado em 8 semanas de TFA. Esta melhora no controle do peso corporal, também foi encontrada em um estudo prévio do nosso grupo, que demonstrou em animais obesos com déficit em leptina isogênicos que o TFA, a partir da terceira semana, foi capaz de produzir melhora no controle de peso destes animais com o protocolo, e estas diferenças foram mantidas até a oitava semana de intervenção, entretanto não foram capazes de produzir melhoras significativas na histologia hepática destes animais como no presente estudo[62].No presente estudo, também foram analisadas variáveis ligadas ao treinamento físico (distância percorrida, tempo de duração e velocidade pico) que foram avaliadas em dois momentos: antes e após as oito semanas de aplicação do protocolo. Elas proporcionam um indicativo de treinabilidade, ou seja, adaptabilidade aos estímulos relacionados ao exercício físico.…”
unclassified